The Role of Crosstalk of Immune Cells in Pathogenesis of Chronic Spontaneous Urticaria - Zhou, Bingjing; Li, Jie; Liu, Runqiu; Zhu, Lei; Peng, Cong (Frontiers in Immunology, 2022)
Chronic spontaneous urticaria (CSU) is defined as recurrent episodes of spontaneous wheal development and/or angioedema for more than six weeks and at least twice a week. The core link in the pathogenesis of CSU is the activation of mast cells, T cells, eosinophils, and other immune cells infiltrating around the small venules of the lesion. Increased vascular permeability, vasodilatation, and recruitment of inflammatory cells directly depend on mast cell mediators’ release. Complex regulatory systems tightly influence the critical roles of mast cells in the local microenvironment. The bias toward Th2 inflammation and autoantibodies derived from B cells, histamine expressed by basophils, and initiation of the extrinsic coagulation pathway by eosinophils or monocytes exerts powerful modulatory influences on mast cells. Cell-to-cell interactions between mast cells and eosinophils/T cells also are regulators of their function and may involve CSU’s pathomechanism. This review summarizes up-to-date knowledge regarding the crosstalk between mast cells and other immune cells, providing the impetus to develop new research concepts and treatment strategies for CSU.